Solar energy for residential housing: A case study of Feed in Tariff (FIT) and Net Metering (NEM) practices in Malaysia - Riyanto, Pitri Wahyuni (Universiti Utara Malaysia, 2019)
Solar energy is one of the natural resources that could be used to contribute to the development of the renewable energy sector in Malaysia. This study is generally aimed to understand in detail about the implementation of Feed in Tariff (FIT) and Net Energy Metering (NEM) practice in order to increase the usage of green electricity which leads to energy efficiency in residential sector. This study hopefully could contribute to the promotion of the renewable energy usage in term of the solar photovoltaic (PV) installation among the residential housing by focusing on the incentive that had been offered by the government such as FIT and NEM. As this study applied an exploratory methodology approach, a semi-structured interview was conducted with an authority body operated in the renewable energy sector in Malaysia. The findings of this study revealed that, by applying FIT and NEM incentives, they provide the homeowners the lower electricity bills every month, offer a passive income, provide an opportunity for homeowners to receive additional bonus of Feed in Tariff rate, as well as assist homeowners to reduce carbon dioxide (CO2) emissions. However, funding and scam in the installation of solar (PV) panels are two main challenges that need to be faced by the Authority in the process of implementing FIT and NEM incentive. Therefore campaign, training and the introduction of solar PV financing are the action that had been taken by the Authority to support the implementation of FIT and NEM incentive for residential sector Malaysia.